Effect of EDTA conditioning on cervical restorations bonded with a self-etch adhesive: A randomized double-blind clinical trial. Issue 9 (September 2015) - Luque-Martinez, Issis; Muñoz, Miguel Angel; Mena-Serrano, Alexandra; Hass, Viviane; Reis, Alessandra; Loguercio, Alessandro D.
Abstract Objective To compare the 18-month retention rates of composite restorations in non-carious cervical lesions [NCCLs] bonded with a self-etch adhesive with and without preliminary conditioning with EDTA. Methods Forty-eight patients with two similar-sized NCCL were selected and randomly allocated to one of two groups. Two calibrated operators placed 96 restorations with a one-step self-etch adhesive (Adper Easy One, 3M ESPE). Half of the restorations were placed according to the manufacturer's instructions while, for the other half, the surfaces of the lesions were conditioned with 17% EDTA for 2 min prior to adhesive application. Two blinded and independent examiners evaluated the restorations at baseline, 6, 12, and 18 months, according to the FDI criteria. The comparison between groups in each period was conducted with the Fisher's exact test, and the performance of each group at the different periods was evaluated by McNemar's test (α = 0.05). Results After 18 months, significantly higher retention rates (95% CI) were observed for the EDTA group (95.5 [84.9–98.7]) than the control group (79.6% [65.5–88.9]) (p = 0.02). Significant deterioration of the marginal adaptation and marginal discoloration were observed for both groups over the 18-month evaluation. Conclusions The preliminary conditioning with EDTA before application of a one-step self-etch adhesive significantly improved the retention rates of composite restorations in cervical lesions. Clinical significance Conditioning with EDTA is an alternative that improves the 18-month retention rate of cervical restorations bonded with a self-etch adhesive.